2000
DOI: 10.1159/000016802
|View full text |Cite
|
Sign up to set email alerts
|

Towards Defining the Role of Glycans as Hardware in Information Storage and Transfer: Basic Principles, Experimental Approaches and Recent Progress

Abstract: The term ‘code’ in biological information transfer appears to be tightly and hitherto exclusively connected with the genetic code based on nucleotides and translated into functional activities via proteins. However, the recent appreciation of the enormous coding capacity of oligosaccharide chains of natural glycoconjugates has spurred to give heed to a new concept: versatile glycan assembly by the genetically encoded glycosyltransferases endows cells with a probably not yet fully catalogued array of meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 157 publications
(167 reference statements)
0
47
0
Order By: Relevance
“…These occurrences indicate that there may be an abnormality in the intercellular responses between maternal uterine epithelium and trophoblast, which may implicate glycan-glycan interactions, as these structures are so abundant at the two apposing cell surfaces. Oligosaccharides are capable of possessing an enormous coding capacity that can mediate cell adhesion (Solís et al, 2001). Whyte and Allen (1985) and Jones et al (2000) have suggested that any aberration of this recognition system may cause a failure in blastocyst attachment at implantation.…”
Section: Discussionmentioning
confidence: 99%
“…These occurrences indicate that there may be an abnormality in the intercellular responses between maternal uterine epithelium and trophoblast, which may implicate glycan-glycan interactions, as these structures are so abundant at the two apposing cell surfaces. Oligosaccharides are capable of possessing an enormous coding capacity that can mediate cell adhesion (Solís et al, 2001). Whyte and Allen (1985) and Jones et al (2000) have suggested that any aberration of this recognition system may cause a failure in blastocyst attachment at implantation.…”
Section: Discussionmentioning
confidence: 99%
“…It is 'the most complex known chemical code in a short sequence among all biological oligomers' (Laine, 1997) and by definition predictive of a host of downstream events. They can be triggered by two principal mechanisms: (i) altering protein folding and routing as well as reactivity with ligands or other proteins, and (ii) acting as biochemical signals decoded by lectins (Sharon and Lis, 1997;Reuter and Gabius, 1999;Solís et al, 2001;Gabius et al, 2004;Honke and Taniguchi, 2009). Hereby, the fundamental functional potential of glycans is broadly realized, giving ample reason for the interest to delineate detailed structure-function relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their strategic cell surface presentation and malignancy-associated structural variability, glycan chains of cellular glycoconjugates deserve attention in this respect. In fact, in the interplay with endogenous lectins, such cell surface determinants participate in regulating cell adhesion, spreading, motility, and mitotic activity (Gabius, 1987(Gabius, , 1997Raz and Lotan, 1987;Varki, 1993;Hakomori, 1998;Kaltner and Stierstorfer, 1998;Reuter and Gabius, 1999;Nangia-Makker et al, 2000;Solı´s et al, 2001;Gabius et al, 2002;Kilpatrick, 2002). By often being positioned readily accessible at the tips of the branches of N-and mucin-type O-glycans, b-galactosides or derivatives thereof harbor ideal features to serve as docking sites for lectins (Gabius, 2000;Brewer, 2002).…”
Section: Introductionmentioning
confidence: 99%